Kearifan Lokal Permukiman Masyarakat Suku Kaili di Desa Taripa, Kabupaten Donggala - Timbang, G.; Malik, S.M.; Julia, F. (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2024)
The settlement is identical to the space and facilities of the general public. The wilderness of the Kaili who settled at the foot of Mount Sidole - the village of Taripa is not deprived of the space and facilities of their settlement physically. Behind the physical reality, there is supposedly a non-physical reality that glides and reinforces the existence of its settlements that are urgently needed to be revealed from the point of view of local wisdom. This research aims to reveal the local wisdom of the Kaili tribal community settlements in Taripa Village, Donggala district. The results of the local Wisdom of Kaili Tribal Settlements at Taripa village are the ability to preserve indigenous culture against external culture, have the capacity to help external cultural elements, able to give direction to the cultural development in the modern society that means social, order and interaction in the life of the community that includes customs, beliefs. Local wisdom on forest conservation in these settlements reflects local wisdom through the settlement ordering process in the dimensions, shapes and layouts of the element of settlement.